Síntese multicomponente de um derivado hexaidroquinolínico - Silva, Larissa da (2021)
A Multicomponent Reaction (MCR) involves a combination of three or more reactants in a single reactions flask in order to obtain a product containing all or a major part of the atoms involved in the reaction. The traditional synthesis requires more laboratory manipulation, as extraction and purification in each reaction step until obtaining the final product, causing a yield loss. The growing concern about environmental issues and the need of making chemical processes less aggressive to the environment, make the MCRs come into focus, because they are done in a single step with a simplified methodology that generates less amount of chemical residues. In the context of the Green Chemistry, the development of organic synthesis through MCR, became a research area of great interest, since in this process has a great atomic economy and efficiency. However, some disadvantage can be listed such as a long reaction time and excess use of organic solvents. In order to solve these problems, heterogeneous catalyst can be incorporated into the methodology. Recently, magnetic iron oxides have been drawing attention in organic synthesis. Its paramagnetic characteristics and insolubility allow easy recovery from the reaction medium. Magnetite nanoparticles are less toxic when compared to other catalyst and have good catalytic efficiency. This project purpose was combine the MCR in solvent-free medium combined with an easy recovery heterogeneous catalysts to obtain products with many application possibilities in less harmful conditions to the environment. The yields of hexahydroquinoline derivatives synthesis were evaluated, using nano particulate magnetite (Fe3O4) as catalyst. The substances were obtained from a mixture of aromatic aldehyde (1 mmol), dimedone (1 mmol), ethyl acetoacetate (1 mmol), ammonium acetate (1.5 mmol) with different amounts of Fe3O4. After the products recrystallization, the catalyst was magnetically isolated and washed several times. The structural characterization was done by NMR 1H and 13C (600 MHz), confirming the identity of the desired product. The results showed that the substances were successfully obtained, the magnetite has the ability to catalyze the synthesis of this class of substances and also allowed to understand and propose how this catalyst works in the synthesis of these compounds. Although more studies are needed to understand what is the best condition to optimize the catalytic activity of Fe2O4 in this reaction, the work shows that this substance has an influence on the yield of hexahydroquinoline formation reaction.